2003
DOI: 10.1074/jbc.c200695200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ubiquitin Fusion System Bypasses the Mitochondria and Generates Biologically Active Smac/DIABLO

Abstract: Smac/DIABLO is a mitochondrial protein that is proteolytically processed and released during apoptosis along with cytochrome c and other proapoptotic factors. Once in the cytosol, Smac protein binds to inhibitors of apoptosis (IAP) proteins and disrupts the ability of the IAPs to inhibit caspases 3, 7, and 9. The requirement for mitochondrial processing and release has complicated efforts to delineate the effect of Smac overexpression and IAP inhibition on cell death processes. In this report, we document a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 48 publications
2
48
0
Order By: Relevance
“…29,30 Of these approaches, we chose the Ub fusion technique (Figure 4a). 30,31 When expressed in HeLa cells, the Ub molecules of these fusion were treated with or without (-) 100 ng/ml TNF for 4 h. Cell lysate samples were prepared from adherent and floating cells, after which the caspase (DEVDase) activity of each lysate sample was measured as described in the Experimental Procedures proteins were almost completely cleaved by endogenous Ubspecific proteases 24 h after transfection, generating DN forms with or without intact IBMs (Figure 4b). Binding between XIAP and each of the mature proteins produced was confirmed by a GST-pull down assay, the results of which indicate that XIAP binds only to proteins with intact IBMs (Figure 4b).…”
Section: Htra2 Cleaves and Inactivates Xiapmentioning
confidence: 99%
“…29,30 Of these approaches, we chose the Ub fusion technique (Figure 4a). 30,31 When expressed in HeLa cells, the Ub molecules of these fusion were treated with or without (-) 100 ng/ml TNF for 4 h. Cell lysate samples were prepared from adherent and floating cells, after which the caspase (DEVDase) activity of each lysate sample was measured as described in the Experimental Procedures proteins were almost completely cleaved by endogenous Ubspecific proteases 24 h after transfection, generating DN forms with or without intact IBMs (Figure 4b). Binding between XIAP and each of the mature proteins produced was confirmed by a GST-pull down assay, the results of which indicate that XIAP binds only to proteins with intact IBMs (Figure 4b).…”
Section: Htra2 Cleaves and Inactivates Xiapmentioning
confidence: 99%
“…Strategies to enhance SMAC expression or the use of SMAC peptides have shown to increase chemosensitivity of several cancers in vitro and in xenograft models. [146][147][148][149] The involvement of the NF-kB pathway in many cancers suggests that inhibition of this pathway might provide new tools to fight cancer. Several in vitro studies have shown that inhibition of the NF-kB pathway could induce apoptosis in myeloma, lymphoma and leukemia patient cells and may be beneficial for the treatment of these malignancies.…”
Section: Iaps As Targets For Cancer Therapymentioning
confidence: 99%
“…24 In mice, on the other hand, targeted deletion of either XIAP 25 or Smac 26 fails to produce an obvious alteration in apoptosis. These latter observations have not only raised questions about the importance of IAP proteins and their antagonists as apoptotic regulators in mammalian cells, but also have been difficult to reconcile with reports that XIAP overexpression inhibits 9,27 and Smac transfection enhances 11,[20][21][22][23]28 the proapoptotic effects of a variety of stimuli in mammalian tissue culture cells.…”
mentioning
confidence: 96%